Tailoring Admittance, Conductance, and Susceptance in TPU/Activated Carbon Films for Flexible Electronics - Kurnaz, Sedat (Gazi University, 2025)
In this study, thermoplastic polyurethane (TPU) composites with varying amounts of activated carbon (AC) (0, 1, 3, 5, 7, and 10 wt%) were fabricated using a solvent-casting method. Scanning electron microscopy (SEM) revealed homogeneous filler dispersion up to intermediate loadings (3-5 wt%), while higher contents (7-10 wt%) led to surface cracks and particle agglomerations. Fourier-transform infrared spectroscopy (FTIR) results showed no evidence of strong chemical bonding between AC particles and the TPU matrix, although minor spectral shifts were consistent with weak physical interactions. Thermal gravimetric analysis (TGA) indicated improved thermal stability at higher AC loadings. Tensile tests showed enhanced mechanical strength up to 5 wt%, though flexibility decreased at higher concentrations (7–10 wt%). Electrical characterization (admittance (Y), conductance (G), and susceptance (B)) from 1 kHz–10 MHzrevealed a clear percolation threshold (~7 wt%), where conductivity sharply increased due to conductive network formation. At 10 MHz, the composite with 10 wt% AC exhibited the highest performance (Y ~114.8 µS, G ~58.8 µS, |B| ~114.1 µS). Jonscher power-law analysis indicated hopping conduction below 7 wt% AC, whereas the 10 wt% sample transitioned into quasi-metallic conduction behavior due to conductive network formation.